2014
DOI: 10.9790/2380-07631823
|View full text |Cite
|
Sign up to set email alerts
|

Technical, Allocative and Economic Efficiency of Pineapple Production in West Java Province, Indonesia: A DEA Approach

Abstract: Low productivity in horticulture is mainly due to the inability of the farmers to exploit the available technologies fully, resulting in lower efficiencies of production. Data Envelopment Analysis (DEA) is used to estimate technical, allocative and economic efficiency also Tobit regression is used to determine factors of technical and economic inefficiency in the pineapple cultivation on 142 farmers in West Java Province, Indonesia. The study has indicated that most of the pineapple farms have shown technical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…The result is consistent with Murthy et al, (2009) and Lubis et al, (2014). The implication is that farmers achieving higher tea yields per hectare can afford better technologies to improve technical efficiency.…”
Section: Determinants Of Smallholder Out-grower Tea Farm Technical Efsupporting
confidence: 82%
“…The result is consistent with Murthy et al, (2009) and Lubis et al, (2014). The implication is that farmers achieving higher tea yields per hectare can afford better technologies to improve technical efficiency.…”
Section: Determinants Of Smallholder Out-grower Tea Farm Technical Efsupporting
confidence: 82%
“…Such results reliably agree on the findings of Balogun, et al (2018) witnessing Nigerian farms' sub-optimal production with the efficiency score of 0.603. In addition, the study by Lubis, et al (2014) affirmed the underperforming farmers in Indonesia who were inefficient in growing pineapples suffering from low mean efficiencies over technical, allocative, and economic measures at 70.1%, 34.1%, and 24.1%, respectively. These comparable findings attested that production inefficiency in farming is likely a global issue.…”
Section: Empirical Results and Discussionmentioning
confidence: 96%
“…With the frontier production function estimation method, Akhilomen et al (2015) estimated the average level of technical efficiency of pineapple producers in Edo State in Nigeria to be 70%. The Data Envelopment Analysis (DEA) method was used by Lubis et al (2014) to estimate the level of technical efficiency of pineapple producers in a province of Indonesia at 70%. Koech et al (2013), in a study of pineapple producers in the Bureti district of Kenya, showed that these producers had an average technical efficiency score of 69%.…”
Section: Discussionmentioning
confidence: 99%